"We are setting ourselves on fire to keep everyone else warm"—what does the recovery look like for NHS staff?. (1st March 2021) - Pagel, Christina; Palmer, Edward
Abstract : Recovery from the pandemic will be as challenging as the pandemic itself, argue Christina Pagel and Edward Palmer